A PUBLICIDADE E AS MINISSÉRIES DA REDE GLOBO: ADAPTAÇÃO E PERSUASÃO - Müller, Karin (2011)
The research aims to understand how Globo TV Network, through the advertisements of its miniseries taken from Brazilian literature, is able to value the product and its image as an institution, emphasizing the literary origin of its production. By informing and pointing out the features of one product through play on words, the advertisements can persuade and seduce the consumer to build up an image that will lead him/her to a purchase and the satisfaction of his/her desire or need. The corpus of this study are the advertisements in the newspaper O Estado de São Paulo, between 1982 and 2008. The methodological procedure used was content analysis. The conclusions support the hypothesis of the research, besides raising the question about the effects of this approach to the TV network.